2017
DOI: 10.17146/jsmi.2017.18.4.4128
|View full text |Cite
|
Sign up to set email alerts
|

Ketahanan Oksidasi Baja Super Austenitik 15%cr-25%ni Pada Temperatur 850 °c

Abstract: KETAHANAN OKSIDASI BAJA SUPER AUSTENITIK 15%Cr-25%Ni PADA SUHU 850 C. Ketahanan korosi suhu tinggi atau ketahanan oksidasi merupakan prasyarat penting bahan logam yang akan diterapkan dilingkungan operasi bersuhu tinggi. Pengujian ketahanan oksidasi baja super austenitik 15%Cr-25%Ni pada suhu 850 C selama 5 jam lebih telah dilaksanakan. Satu sampel as-cast sebagai acuan awal yang tidak diperlakukan panas dan dua (2) kelompok sampel (masing-masing 3 buah) disiapkan dalam eksperimen. Satu kelompok sampel as-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…This sample is likely to be easily attacked by environmental corrosion faster than other samples (experiencing earlier fragility). This high temperature corrosion rate in steel materials has been discussed in the literature [6]. Figure 4 shows the optical microstructure of steel (a) as-cast and (b) annealed sample with 100x magnification.…”
Section: Crystal Structurementioning
confidence: 62%
See 2 more Smart Citations
“…This sample is likely to be easily attacked by environmental corrosion faster than other samples (experiencing earlier fragility). This high temperature corrosion rate in steel materials has been discussed in the literature [6]. Figure 4 shows the optical microstructure of steel (a) as-cast and (b) annealed sample with 100x magnification.…”
Section: Crystal Structurementioning
confidence: 62%
“…The average rigidity of this material is around 160 HVN (84 HRC). A recent study reported that A2 type steel showed very good corrosion rates, almost 0.088 mm per year [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average hardness of this material is approximately 160 HVN (84 HRC). A recent study reported that this type of steel showed good corrosion rates, i.e., approximately 0.088 mm/year [4], and was resistant to oxidation at 850 °C [5]. One of these characteristics can be influenced by the formation of the crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The ferritic steel has been reported to have the super alloy phenomenon as regards its corrosion resistance [4], hardness, and tensile-impact strengths [5]. The main objective of synthesizing the new ferritic alloys is to significantly improve the corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%